1996
DOI: 10.1210/endo.137.4.8625885
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of glucose availability suppresses pulsatile luteinizing hormone release in female and male rats.

Abstract: Glucose availability controls reproductive activity through modulation of LH secretion. The aim of the present study was to determine whether the glucoprivic suppression is potentiated by gonadal steroids and if glucoprivic suppression of pulsatile LH release is sexually differentiated. Pulsatile LH secretion was examined in rats after peripheral (jugular) administration of the competitive inhibitor of glycolysis, 2-deoxyglucose (2DG). Fourteen days after gonadectomy, blood samples were collected every 6 min f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(48 citation statements)
references
References 6 publications
1
45
0
2
Order By: Relevance
“…The glucose availability has been proposed to modulate GnRH secretion [13, 25, 26]. Suppression of pulsatile LH secretion has been documented under low insulin levels despite high glucose levels in streptozotocin-induced diabetic rats [27], though it remains unclear if neural cells monitoring glucose availability to regulate GnRH are sensitive to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The glucose availability has been proposed to modulate GnRH secretion [13, 25, 26]. Suppression of pulsatile LH secretion has been documented under low insulin levels despite high glucose levels in streptozotocin-induced diabetic rats [27], though it remains unclear if neural cells monitoring glucose availability to regulate GnRH are sensitive to insulin.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have shown the existence of a dose-dependent response to orexins, but have also suggested a modulatory role of estrogen in this response. In support of the latter view, there is general agreement that suppressive actions of fasting, insulin injection, and 2-deoxyglucose injection on pulsatile LH secretion are significantly greater in the presence of a small dose of estrogen than in its absence in OVX animals [13, 14, 15, 16]. …”
Section: Introductionmentioning
confidence: 91%
“…Instead of, or in addition to, hormonal signals, signals generated by the oxidation of metabolic fuels are critical for normal reproductive function. For example, inhibition of glucose oxidation inhibits oestrous cyclicity in intact, well‐fed Syrian hamsters (30), alters oestrogen‐receptor distribution and the duration of oestrous behaviour in steroid‐primed, ovariectomised hamsters (31), and suppresses pulsatile LH secretion in well‐fed rats (32) and ewes (33). During food restriction, profound changes in circulating metabolic fuels occur as fuel utilisation shifts from oxidation of carbohydrates derived from ingested food and liver glycogen to utilisation of fuels from long‐term stores of lipids in adipose tissue.…”
mentioning
confidence: 99%